Uma contribuição da geografia da saúde para o estudo da dengue no Município de Anchieta (ES) - Pedrosa, Eduardo Batista (2011)
This research was developed from an analysis of the situation regarding the distribution and spatial dispersion of dengue in the state of Espírito Santo, where it was found the worsening situation in sparsely populated counties, and directed the focus of research for this type the municipality, and the city of Anchieta shrunk to the final realization of the research. Whereas the approaches in Health Geography offer a range of tools and theoretical concepts and little explored by geographers, we sought to contribute to the inclusion of studies on the health and well being of people in Geography. Thus, in principle, an analysis was performed using quantitative tools, thematic maps and graphics, which led us to check some spatial conformations of dengue in the Holy Spirit. After the first stage sought to humanistic perspective within the Health Geography , through a qualitative research to evaluate the production of sense and analyze the narratives of the agents of environmental surveillance in the city of Anchieta.